Empowering Healthcare Professionals: an Effort to Enhance Sexually Transmitted Disease Knowledge - Prakoeswa, Flora Ramona Sigit; Sari, Winda Atika; Hidayat, Saiful; Romadhon, Yusuf Alam (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Sexually transmitted diseases (STDs) present a significant challenge in the public health field. Health professionals are at the forefront of controlling the transmission and management of this disease; hence, efforts to update knowledge regarding STDs are very important for this group. Purpose: This study aims to explain the effect of integrated counseling on increase STD knowledge in an effort to prevent the occurrence of sexually transmitted diseases. Methods: We carried out health education activities containing material related to aetiology, modes of transmission, risk factors, risk groups, and therapy for sexually transmitted diseases at one hospital in Surakarta. The Sexually Transmitted Disease Knowledge Questionnaire (STD-KQ) was used to assess participants' knowledge regarding STDs, which was distributed before and after giving the material. The difference in STD-KQ scores before and after the counselling session was analysed using the Wilcoxon Test. Result: Prior to the counselling session, 22 (32.83%) participants had poor knowledge, 41 (61.19%) had moderate knowledge, and only 4 (5.97%) possessed a good understanding of STDs. Following the counselling session, there was a noteworthy improvement in knowledge levels, with 47 (70.14%) participants now classified as having good knowledge. Additionally, 18 (26.86%) participants maintained a moderate level of knowledge, while 2 (2.98%) retained poor knowledge. The analysis showed that the difference was statistically significant (P value < 0.001).